2021
DOI: 10.3892/ol.2021.12657
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑223‑5p suppresses the progression of nasopharyngeal carcinoma by targeting DCLK1

Abstract: The aim of the present study was to investigate the function of microRNA (miR)-223-5p in the malignant biological behavior of nasopharyngeal carcinoma (NPC) and elucidate the underlying molecular mechanism. The expression levels of miR-223-5p and doublecortin-like kinase 1 (DCLK1) were detected via reverse transcription-quantitative PCR analysis. Cell viability was evaluated using Cell Counting Kit-8 assay. Cell migration and invasion were measured via Transwell assays, while a luciferase reporter assay was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…DCLK1 is a transmembrane microtubule-associated protein kinase with a DCX domain and a C-terminal serine/threonine protein kinase domain, which is considered to be a crucial modulator of cell movement [30]. Previous studies have shown that DCLK1 is highly expressed in a variety of cancers and has been identified as a potential oncogene associated with cancer progression, in intestinal tumor, non-small cell lung cancer and nasopharyngeal carcinoma [31][32][33][34]. In addition, there are a large number of reports about the role of DCLC1 in PC.…”
Section: Discussionmentioning
confidence: 99%
“…DCLK1 is a transmembrane microtubule-associated protein kinase with a DCX domain and a C-terminal serine/threonine protein kinase domain, which is considered to be a crucial modulator of cell movement [30]. Previous studies have shown that DCLK1 is highly expressed in a variety of cancers and has been identified as a potential oncogene associated with cancer progression, in intestinal tumor, non-small cell lung cancer and nasopharyngeal carcinoma [31][32][33][34]. In addition, there are a large number of reports about the role of DCLC1 in PC.…”
Section: Discussionmentioning
confidence: 99%